Maternal nutritional knowledge and its association with iron deficiency anemia in children - Ismail, Ameera; Fahima Fatima (International Journal of Endorsing Health Science Research, 2018)
Background: Young children are more prone to the development of Iron Deficiency Anemia (IDA). The most important factor of IDA in children is maternal nutritional knowledge because mothers are the sole source for providing diets to their children. Therefore, this study was intended to assess the maternal knowledge of child nutrition, hemoglobin (Hb) status of children and effect of maternal knowledge of anemia on its prevalence in children. Methodology: A cross-sectional study was conducted to evaluate the prevalence of anemia in young children. In total, 143 pairs of children (2 – 10 years) along with their mothers were randomly selected. Data was collected by conducting interviews from mothers, using a structured questionnaire for their knowledge on child nutrition. Portable hemoglobinometer was used for identifying the Hb status of children. Data was analyzed using Statistical Project of Social Science (SPSS) version 22. Result: It was evaluated that 4 out of 5 children were anemic. Out of total participant in the study, 7.69% of mothers were found to have a poor nutritional knowledge and all of their children were anemic. Approximately 63.64% mothers had average knowledge and 86.8% of their children were anemic while the rest were okay. Moreover, 28.67% of mothers with high nutritional knowledge had 58.5% anemic children and the rest was fine. The relationship between maternal nutrition knowledge and Hb level of children was highly significant (p<0.001). Conclusion: Maternal knowledge about nutrition is associated with the prevalence of anemia in their children and it is one of the major modifiable factors.